Coronary stent failure in patients with diabetes: A nationwide observational study from SWEDEHEART - Irene Santos-Pardo (17607279) (2025)
Objective: The association between diabetes and coronary stent failure is poorly established with second-generation drug-eluting stents (DES). We aimed to evaluate the risk of stent failure in patients with diabetes compared to subjects without diabetes after implantation of second-generation DES. Research design and Methods: All patients in Sweden who received second-generation DES between 2010 and 2020 were included and categorized into three groups: type 1, type 2 diabetes, and subjects without diabetes (reference group). The primary endpoint was stent failure, defined as in-stent restenosis or stent thrombosis. Adjusted hazard ratios (HR) with 95% confidence intervals (CI) were estimated by Cox regression models. Sensitivity analyses were performed to address missing data in covariates and account for death as a competing risk. Results: The study included 160,523 patients: 2,406 with type 1, 43,377 with type 2 diabetes and 114,740 without diabetes. Seventy-one percent were male. Over a mean follow-up of 4.5 years, 5,510 stent failure events occurred. The fully adjusted HR for stent failure was 2.28 (95% CI 1.97–2.65) for type 1 and 1.35 (95% CI 1.27–1.44) for type 2 diabetes, compared to subjects without diabetes. Sensitivity analyses confirmed the robustness of the findings, with both in-stent restenosis and stent thrombosis contributing to the increased risk. Conclusion: We observed a significantly higher risk of second-generation DES stent failure in individuals with type 1 diabetes followed by those with type 2 diabetes, compared to subjects without diabetes. This elevated risk was attributed to both in-stent restenosis and stent thrombosis.